The Charité III Artificial Disc lumbar disc prosthesis: assessment of medium-term results - Gioia, G. (J Orthop Traumatol, 2007)
The intervertebral disc prosthesis seems to have gained its place in spinal surgery. The first 45 disc replacements (36 patients) performed at our institution have been followed for 5–9 years with standard radiography, CT, MRI and clinical evaluation. Two prostheses failed and needed further surgery. The mean Oswestry Disability Index score dropped from 44% to 9% and the pain score recorded on a visual analogic scale (VAS) dropped from 8 to 1.4. 92% of patients had excellent or good results and gave a positive answer to the question “Would you be ready to sustain again this same surgical procedure?” In 4 cases, a tendency towards prosthesis subsidence was observed. With time, 6 patients showed periprosthetic calcifications. One patient developed retrograde ejaculation. In conclusion, intervertebral disc prosthesis is a well established procedure that achieves good mid-term results, but doubts still remain about the longterm outcome. Care about right indication, eventual complications and assessment of long-term results are key points for the future of this procedure.